ROBUST PLANNING FOR COMBINED HEAT AND POWER PRODUCTION. Issue 30 (2015) - Faille, D.; Fouquet, M.; Péchiné, B.; Ahallal, S.; Ghaoui, L. El; Pauphilet, J.
Abstract: Combined Heat and Power Plants which produce simultaneously electricity and heat are known for their energetic efficiency. Associated to heat storage, they may also be a solution to adapt the electricity production to the demand. Flexibility of the generation and consumption will be indeed a driver for the development of the Renewable, and electricity prices are already used as an incentive by DSO to modulate the electricity demand. As the electricity prices vary substantially depending on the weather conditions, a real-time optimization is desirable to generate an optimal planning of the Combined Heat and Power Plant load. Moreover the heat demand cannot be exactly forecast and the planning must remain valid against this uncertainty. In this paper we present a solution based on convex optimization to produce robust planning for CHP.